Sono-electrochemical degradation of Orange G in pure water, natural water, and seawater: effect of operating parameters. Issue 47 (7th October 2016) - Lounis, Manel; Samar, Mohamed Elhadi; Hamdaoui, Oualid
Abstract: Sono-electrochemical degradation of Orange G (OG) in acidic aqueous solutions using 22.5 kHz ultrasonic irradiation with platinum grid anode and carbon felt cathode was investigated. Effects of various operating parameters such as ultrasonic power, initial pH, initial dye concentration, electric current, and Fe(II) concentration on the degradation of OG were examined. Additionally, sono-electrochemical degradation of substrate was evaluated in natural mineral water and seawater. The obtained results show that the degradation increased with increasing ultrasonic power up to 15 W. Significant degradation was achieved at pH 3 with an applied current of 100 mA and a Fe(II) concentration of 0.05 mM. It was found that sonoelectrofenton process is an efficient technique for the degradation of OG even in complex matrices such as natural mineral water and seawater. Its high performance arises from the coupling between ultrasound irradiation and the in situ electrogeneration of Fenton's reagent. A significant synergy index of 4.5 was observed for the sono-electrochemical treatment of water contaminated by OG.